Effect of Augmented Reality Flash Card Media on Reading Interest and Storytelling Ability in Children Aged 5-6 Years - Ruswanti, Titien; Jannah, Miftakhul; Fitri, Ruqoyyah; Kristanto , Andi; Dewi, Utari; Lasarus , Yes Matheos (International Journal of Emerging Research and Review, 2025)
Objective: This study is to determine the influence of media Flash Card Augmented Reality on Reading Interest and Storytelling Ability of 5-6 Years Old Children. Method: This research is quantitative research experiment with design Nonrandomized Pretest-Posttest Control Group Design experiment, the research subjects were 50 children divided into 2 groups, namely the experimental group of 28 children, with 9 boys and 19 girls, the control group of 22 children, with 11 boys, 11 girls so that the total number of boys was 20 children or 40% and girls 30 or 60%, with an age range of 5-6 years, the instrument used was an observation sheet for reading interest and storytelling ability. The data analysis technique used test Mann-Whitney U test. Results: This study shows a significant level where the p score shows a result of less than 0.001, that there is a difference in gain score between the experimental group and the control group. This shows that because there is a difference between the control group and the experimental group, it means that there is an Influence of Flash Card Augmented Reality on Reading Interest and Storytelling Ability of Children Aged 5-6 Years. Novelty: Through the fun Augmented Reality Flashcard media mechanism, it triggers children's interest in reading and storytelling skills. Through this study, it is expected to find empirical evidence regarding the benefits of using augmented reality-based flashcards, as well as provide recommendations for educators in improving the quality of learning in the classroom.